Investigating the Effectiveness of Using Virtual Reality to Improve Vocational Students Ability in English Descriptive Writing - Sitorus, Nurianti; Sinambela, Yusnia; Juwairiah, Juwairiah (Proceeding International Conference on Religion, Science and Education, 2025)
English as a global language has shifted its teaching method to technological aid with virtual reality as an alternative to do so. Virtual reality (VR) has been long known as one of the method in teaching particularly for vocational students. It let the learners to undergo a computer-generated environment that seems to be real and interact with it immediately. However, only few studies have investigated the effectiveness of integrating virtual reality to improve vocational student’s ability in writing descriptive text in English. Writing performance is one of the indicators whether the students mastering English or not. Based on that reason, teaching them descriptive writing will give useful knowledge as long as to train them to master technique in writing. One of the prominent genres in English writing is descriptive writing. Descriptive writing is used mostly to describe an object, person, place specifically. This current study aims to investigate how far virtual reality can be used to improve the ability of vocational students in writing descriptive text. The researchers would employ several objects in virtual world which provides sources for the participants to learn about descriptive text. The mixed-method approached was used combining with pre- and post-test surveys and semi-structured interviews. Participants are 22 English learners from the third semester majoring in Graphic Design who are studying English for Specific Purpose (ESP). The result demonstrated that albeit the majority of students took pleasure in using virtual reality, they intended to have various attitudes regarding the advantage of using it in the studying process. Moreover, the outcomes from a correlation analysis indicates that learners’ attitudes towards the materials being learned (ESP writing) remarkably corresponding to students’ attitudes towards using virtual reality (VR).